齿轮连杆组合机构的交互式图形仿真设计 - 高洪; 赵雪松; 吕新生 (Jixie chuandong)
Appling the theory of machines and mechanisms, a mathematical model was established for the design of a typical gear-linkage combined mechanism. In the course of solving the mathematical model, a design procedure named interactive design of graphic simulation was proposed, which use three-dimensional graphic simulation to watch and analyze the overall property and the distribution of its solution, and then use two-dimensional graphic simulation to search out its local solution. Finally, it was pointed out by an example that the procedure can not only unify logical thinking and thinking in image, but also unify overall solution and local solution.